(untitled) (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Around 70-80% diagnoses are based upon laboratory medicine. Traditionally, laboratory medicine subjects like Biochemistry, Pathology and Microbiology were limited to the first two years of Bachelor of Medicine and Bachelor of Surgery (MBBS) basic sciences curriculum. With recent advances and its significant roles, laboratory medicine is being included in the clinical years as well. Patan Academy of Health Sciences (PAHS) has included laboratory medicine curriculum in clinical year. This study aimed to know the perception of interns on laboratory medicine curriculum in the clinical practice. Method: This was a descriptive cross-sectional study conducted among intern students of fifth batch of School of Medicine, PAHS. Ethical clearance was taken from the Institutional Review Committee, PAHS (Ref No: drs2007091393). Research questionnaires were constructed and validated by faculties of laboratory medicine. A total of 43 out of 65 Interns had responded the questionnaires emailed. Responses were noted on four point Likert scale as strongly agree, agree, disagree and strongly disagree. Result: A total of 26(60.47%) interns had strongly agreed and 14(32.56%) had agreed that they perceived the importance of filling laboratory requisition form with all the required information. A total of 37(86.03%) interns had agreed that they were aware about possible errors that can occur in laboratory testing procedures. A total of 36(83.72%) interns had agreed that they felt free to communicate with lab personnel when lab report did not correlate with clinical features. Conclusion: Interns perceived that the lab medicine curriculum learning was beneficial to them for understanding of the laboratory process and its importance in patient diagnosis and management.